Effect of Metarhizium anisopliae in some biological aspects of the greater wax moth Galleria mellonella (L.)(Lepidoptera:Pyrallidae ) - Reddah Annon, Mohammed; Ibrahim Jasim, Muna (Al-Qadisiyah Journal of Pure Science, 2018)
Different concentrations of the fungal suspension of Metarhizium anisopliae have been used against different stages of Galleria mellonella ( L.) . The highest percentage of eggs mortality reached 62.88 % at the concentration of 1×107 spore/ml and decreased to 31.78 % at the concentration of 1×104 spore/ml , The value of LC50 of eggs was 1×105.82. The larval instars have showed highest mortality rate reached (100 , 96.99 and 90.97 ) % for 1st , 4th and 7th larval instars respectively during 120 h at the concentration of 1×107 spore/ml , The values of lowest mortality rate when treated with the concentration 1×104 spore /ml during 120 h were (62.90 , 58.88 , 50.86 ) % for 1st , 4th and 7th larval instars respectively , The values of LC50 were (1 × 103.72 , 1 × 103.86 , 1 × 103.99 ) spore/ml for 1st , 4th and 7th larval instars respectively after 120 h . 54.89 % the highest mortality rate for the pupae when exposed to 1×710 spore /ml and 36.85 % were dead when exposed to 1×410 spore /ml , The LC50 was 1 × 106.18 . The relationship between fungal suspension concentration and rate of adult mortality took the same trend , and the treatment with highest concentration caused a high adult mortality, i.e 69.95 % and 63.94 % for adult males and females at 168 hours, while the lowest mortality percentages were 41.91 % and 43.91 % when treated with 1×10 4 spore/ml at the same time, indicating that the males were more readiness than females to the fungal suspensions , The values of LC50 were (1 × 104.77 and 1 × 105.11 ) spore/ml for males and females respectively .